O papel do narrador na literatura e no cinema: Estorvo, de Chico Buarque e Ruy Guerra - Santos, Carlos Roberto da Silva (2011)
This study aimed at comparing the role of the narrator in the novel Estorvo (1991) by Chico Buarque and Ruy Guerra is movie (2000) with of the same title. It is makes use of theories involving the structure of the literary and cinematic narrative. The narrator's literary and film is perceived as the role of the narrator is exercised in literature and film and how its passage to the language of film is altered according to the behavior of the agent of the narrative. The narrator and his role are outstanding issues from the beginning of the twentieth century. Its theirs behavior in the telling of the tale is revealed by the characteristics of the characters that are unfolded through the agent of the narrative. Wayne Booth (1983) in Rhetoric of fiction also takes into account non-formal elements in their interdependence with the formal. We analyzed original notions serch as the implied author, and unreliablity and the distance of fiction. Booth also examined how the argumentative structures of the text were significant to the reader. The various functions and roles of the narrator are in Booth of primary importance because it is the consciousness that the narrator has, there is adaptation in perspective and the meaning of the narrated. To this end the fundamentals of Genette (1976), the aforementioned Booth (1983), Chatman (1990), Stam (2008), Bouillon (2009) and Friedman (1985), among many other critics and theorists of literary narrative and cinematic are relevant to this work.